(untitled) (UNIZIK Journal of STM Education, 2023)
This study examined experiential learning strategy and students’ performance in Mathematics on the cognitive domain of Bloom’s Taxonomy. Two research questions and two hypotheses guided the study. Quasi-experimental design, specifically pretest, posttest non-control group design, was adopted for the study. The population of the study consisted of 13,040 SS2 Mathematics students from 14 public secondary schools in Obio-Akpor Local Government Area, Rivers State out of which, a sample of 78 was drawn from the schools using purposive sampling based on availability and access to adequate facilities for Mathematics teaching and learning. Random sampling was used to select the intact classes for the study. The experimental groups were taught using the experiential learning strategy and while the control group was taught using the lecture teaching method. Mathematics Performance Test (MPT) was used for data collection. A reliability Coefficient of 0.79 was obtained for the instrument using Kudar Richardson 21. Research questions were answered using mean and standard deviation while Analysis of Covariance (ANCOVA) was used to test the hypotheses at 0.05 level of significance. Findings of the study revealed that students taught Mathematics using experiential learning strategies performed better than their counterparts taught with the lecture teaching method at the comprehension and application level. The study recommends among others that the lecture teaching method of teaching should be adopted to the use of an experiential learning strategy so as to improve the mathematics performance of students at both comprehension and application levels.